Laser cleaning on severely corroded steel members: Engineering attempt and cleanliness assessment. (20th November 2022) - Wang, Qidi; Kainuma, Shigenobu; Zhuang, Shusen; Shimizu, Kiyoshi; Haraguchi, Manabu
Abstract: A highly effective, environmentally friendly, high-power continuous-wave laser (CWL) transmitter was newly developed to remove corrosion products from severely corroded steel structures. In this regard, treatment conditions of dry laser cleaning (DLC) and wet laser cleaning (WLC) of the drench, soak, and rinse methods are adopted, and the cleanliness effect is compared with that of conventional abrasive blasting treatment. The morphologies and chemical compositions of untreated and treated surfaces are analyzed using three-dimensional digital microscopy, laser confocal microscopy, and scanning electron microscopy–energy dispersive X-ray spectrometry. The results show that laser cleaning can efficiently remove corrosion products and salts that severely corrode steel members, as well as prolong the re-corrosion time of the cleaned surfaces. WLC can achieve excellent microscopic cleaning and reduce the effect of high-temperature inputs on the surface via laser irradiation. Further mechanistic analysis indicates that ablation, melting, and evaporation during laser cleaning primarily contribute to the removal of corrosion products and salts. As a result, the WLC drench method yields the best surface cleanliness and is suitable for practical engineering applications. This study provides a basis for maintaining severely corroded structures via laser-cleaning techniques.